Analysis of Learners’ Classroom Interaction Using Listing and Comparing Task in English Study Program of Cenderawasih University Teaching Context - Gultom, Monika (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2019)
The main focus of this research is the analysis of interactions between students (learner-to-learner interaction) in the context of cooperative learning through pair-group learning activities. The pair-group learning activities were provided to make sure the intense of the interaction that focus on doing the ordering, task listing, and problem solving tasks. This current research uses descriptive qualitative method by collaborating with students as the subject of this study acting as a key instrument in order to collect data as authentically as possible in the data collection of interactions that occur between students through voice recording. The results showed that the interaction occurred in within the English language education study program FKIP UNCEN are still dominated by lecturers, such as asking questions, error corrections, lectures, explained and waiting for the learners’ response, and therefore suggested to create an encouraged atmosphere of activeness and participation regarding the kinds of learning activities that "force" students to interact in smaller groups to ensure the equal opportunities to interact within the group using cooperative learning activities with a focus on ordering task, listing task, and problem solving task.